Investigating the effects of sintering additives and heating regimes on the performances of glass–ceramic proppants derived from industrial wastes - Jincai Zhang; Yueting Fan; Xubo Zhai; Vishnu Vijay Kumar (Materials & Design)
This article aims to explore a simple and effective method of preparation industry solid waste based ceramic proppant and elucidate the sintering mechanism for prompting further study in the future. Glass-ceramic-based proppants were successfully fabricated using fly ash and kaolin, as main raw, matching other raws and additive such as TiO2 and Fe2O3, in lab. The results showed that the proppants had the optimum overall performances when the total content of SiO2 and Al2O3 was at 85 %, their molar ratio was 1, with a sintering temperature of 1250℃. The heating rate and the holding time were 2.5℃/min and 90 min, respectively, with the addition of 3 % TiO2 and 5 % Fe2O3. The cylinder compressive strength of the samples increased 73.33 % by following step-by-step optimizations than origin sample. Furthermore, the sintering mechanism was elucidated and all possible chemical reaction were explored at the high temperature sintering process. The additives such as TiO2 and Fe2O3 prompt the crystal melting and amorphous as well as mullite formation, which made raw solid particle set change into a glass–ceramic-based whole body. New finding indicates the new phase formation and their content inside proppant body have an important contribution to the enhance of the cylinder compressive strength.